Entre exploitation et protection : la question forestière au cœur d’une ambivalence historique au Brésil - Marion Daugeard; Paulo Roberto Cunha (Caravelle)
The study of the construction and evolution of Brazilian forestry legislation’s allows us to retrace the way in which elites and governments historically considered the use of forests and other forms of vegetation. This article highlights the ambivalent character of this process and thus proposes an original approach to analyse the current issues at stake in Brazil, in the time of the Anthropocene.